ASSISTING LYN'Z HEALTH & BEAUTY CARE FOR TRADEMARK REGISTRATION AS AN EFFORT TO PROVIDE INTELLECTUAL PROPERTY RIGHTS - Cindy Anggelia; Hari Sutra Disemadi (ConCEPt - Conference on Community Engagement Project, 2022)
Law Number 20 of 2016 concerning Marks and Geographical Indications in Article 1 Paragraph 1 explains that a mark is a sign that can be displayed graphically in the form of images, logos, names, words, letters, numbers, color arrangements, in 2 (two) dimensions. , sound, hologram, or a combination of two or more of these elements to distinguish goods and/or services produced by persons or legal entities in the activities of trading goods and/or Services. Lyn'z Health & Beauty Care is a business engaged in health and beauty services. The reason for the owner of the brand is notregistering the "Lyn'z Health & Beauty Care" Brand yet is because the ownerof brand is unfamiliar with the trademark registration procedure, which is can conducted online via the DJKI website. Therefore,to do proper mark registration, it is necessary to provide assistance. The purpose of this community service is to register the MSME brand. There are 3 stages that used for implementation method., First stage is to identify problems owned by partner , The second stage is to have a preparation for solving partner problem and the And the third stage is implementation . The result of this community service is the registration of the Lyn'z Health & Beauty Care MSME brand, as provenby the receipt of an online application for the Lyn'z Health & Beauty Care Mark registration